Compatibility of a model for the QCD-Pomeron and chiral-symmetry breaking phenomenologies - Natale, A. A. [UNESP]; Rodrigues Da Silva, P. S. [UNESP] (Elsevier, 1997)
The phenomenology of a QCD-Pomeron model based on the exchange of a pair of non-perturbative gluons, i.e. gluon fields with a finite correlation length in the vacuum, is studied in comparison with the phenomenology of QCD chiral symmetry breaking, based on non-perturbative solutions of Schwinger-Dyson equations for the quark propagator including these non-perturbative gluon effects. We show that these models are incompatible, and point out some possibles origins of this problem.